Mis primeros-- numeros - Sanchez Sanchez, Isidro; Elena, Horacio (New York : Barron's, 1991)
Introduces the numbers from one to nine and provides the reader with the opportunity of counting such things as animals, flowers, balloons, and umbrellas.
Keywords: Numeration -- Juvenile literature; Counting; Spanish language materials